KEMANGKUSAN MODEL PEMBELAJARAN KHAYALAN DAN MODEL PEMBELAJARAN RODRIGUES-BADACZEWSKI DALAM PEMBELAJARAN MENULIS CERPEN PADA SISWA SMP - Amrulloh, Muhammad Hanif (Diksi, 2017)
Penelitian ini bertujuan untuk (1) mengetahui apakah ada perbedaan tingkat keterampilan menulis cerpen yang signifikan antara pembelajaran siswa yang menggunakan model pembelajaran Khayalan, model pembelajaran Rodrigues-Badaczewski, dan model pembelajaran konvensional ; (2) menguji apakah penggunaan model pembelajaran Khayalan dan model pembelajaran Rodrigues-Badaczewski mangkus digunakan dalam pembelajaran menulis cerpen pada siswa kelas VII di SMP Negeri se-Kabupaten Brebes. Penelitian ini merupakan penelitian kuantitatif dengan metode penelitian eksperimen. Desain penelitian ini adalah pretest posttest control group design. Simpulan penelitian ini berdasarkan analisis tersebut adalah (1) ada perbedaan tingkat keterampilan menulis cerpen yang signifikan antara pembelajaran siswa menggunakan model pembelajaran Khayalan dan model pembelajaran konvensional; (2) ada perbedaan tingkat keterampilan menulis cerpen yang signifikan antara pembelajaran siswa menggunakan model pembelajaran Rodrigues-Badaczewski dan model pembelajaran konvensional; (3) tidak ada perbedaan tingkat keterampilan menulis cerpen yang signifikan antara pembelajaran siswa menggunakan model pembelajaran Khayalan dan model pembelajaran Rodrigues-Badaczewski; (4) penggunaan model pembelajaran Rodrigues-Badaczewski dan model pembelajaran Khayalan mangkus digunakan dalam pembelajaran menulis cerpen pada siswa kelas VII SMP Negeri se-Kabupaten Brebes.Kata Kunci: kemangkusan, model pembelajaran Rodrigues-Badaczewski, model pembelajaran khayalan, menulis cerpen, siswa SMP THE EFFECTIVENESS OF IMAGINE LEARNING MODEL AND RODRIGUES-BADACZEWSKI LEARNING MODEL IN SHORT STORY WRITING LEARNING ON GRADE VII STUDENT IN JUNIOR HIGH SCHOOL IN BREBES REGENCY ABSTRACTThe research aimed to (1) research the significant differences of short story writing skill among students who learn it by Imagine learning model, Rodrigues-Badaczewski learning model, and conventional learning model; (2) examine the effectiveness of Imagine learning model and Rodrigues-Badaczewski learning model in writing learning on grade VII students in junior high school in Brebes Regency. This research is experimental research using pretest-posttest control group design. The result brings to the conclusion that (1) there is a significant difference of short story writing skill between students who learn it by Imagine learning model and conventional learning model; (2) there is a significant difference of short story writing skill between students who learn it by Rodrigues-Badaczewski learning model and conventional learning model; (3) there is not a significant difference of short story writing skill between students who learn it by Rodrigues-Badaczewski learning model and Imagine learning model; (4) Rodrigues-Badaczewski learning model and Imagine learning model are effective for short story writing learning on grade VII students in junior high school in Brebes Regency. Probability value on 0.000 (p<0.05) obtained from Scheffe variant analysis on posttest data of control group and first experimental group and probability value on 0.000 (p<0.05) obtained from Scheffe variant analysis on posttest data of control group and second experimental group.Keywords: effectiveness, Rodrigues-Badaczewski learning model, Imagine learning model, short story writing, Junior High School students.